Qualidade de vida e funcionalidade de alunos com paralisia cerebral matriculados na escola regular - Sanchez, Gabrielle Cristina (Universidade Federal de São Carlos, 2018)
Cerebral palsy (PC) affects children and young people, with prevalence in developing countries and causes motor impairment that can limit movement and postural maintenance independently and autonomously. In this way, people with CP may have a low achievement rate in daily activities, such as in the context of the school. Although the discussion about inclusion in the present day is broad, the participation of students with cerebral palsy in the common classes of regular schools is still challenging, which may significantly reflect on the functional capacity and quality of life of these students. Thus, this study aimed to analyze the Quality of life (QoL) and Functionality of students with cerebral palsy in the regular school of a medium-sized city in the interior of São Paulo and to verify if there is a relationship between QoL and Functionality variables. Three students with cerebral palsy, enrolled in the public elementary school, aged nine to twelve, with three mothers, and two teachers of the Specialized Educational Assistance (AEE) attending the students in the room participated in the study. multifunctional features (SRM). In order to perform the data collection, a questionnaire to evaluate the quality of life that was answered by the teachers and the students (CP-QOL-child) was used as a research tool, and a scale that evaluates the student's functionality in the school, which was answered by the School Function Assessment (SFA) teachers. Data triangulation was performed for descriptive and qualitative analysis. The results showed that there is no relation between the functionality and the quality of life for each of the students with PC. Still, the general view on QOL was positive, however, many answers were opposed between mother and daughter, which leads to different perceptions of the same domain of QoL. Thus, the students participating in the study were satisfied with regard to the adaptations and assistance that are made available to them in the school, in which they are able to enjoy the spaces by participating actively in the activities. In addition, QoL should be discussed in order to cover the entire daily context of the person with PC, so that further analysis is possible, in order to create strategies for the improvement of QoL and the Functionality of people with PC.
Quality of life and functionality of students with cerebral palsy enrolled in regular school
Keywords: Funcionalidade; Educação especial; Paralisia cerebral; Qualidade de vida; Special education; Cerebral palsy; Quality of life; CIENCIAS HUMANAS